2005
DOI: 10.4315/0362-028x-68.10.2095
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Fumonisin B1 and Zearalenone by Lactic Acid Bacteria in Fermented Maize Meal

Abstract: Fusarium species are fungi that infect maize products worldwide and elaborate mycotoxins, which have been associated with cancer. This study was carried out to investigate the potential of lactic acid bacteria fermentation in reducing mycotoxin concentration and toxicity in maize meal products. Maize meal was spiked separately with fumonisin B1 and zearalenone and then allowed to ferment for 4 days. The potential cytotoxicity of the mycotoxin-spiked fermented extracts was also investigated using the SNO human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
54
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 23 publications
9
54
0
1
Order By: Relevance
“…Ström et al (2002) explains this effect as bacterial additives containing Lactobacillus plantarum and producing metabolites that inhibit growth of moulds and production of mycotoxins. The results of Mokoena et al (2005) indicate that lactic acid bacteria fermentation can significantly reduce the concentration of fumonisins and zearalenone in maize. The positive effect of Lactobacillus on mould growth and aflatoxin production was reported by Gourama and Bullerman (1995).…”
Section: Discussionmentioning
confidence: 86%
“…Ström et al (2002) explains this effect as bacterial additives containing Lactobacillus plantarum and producing metabolites that inhibit growth of moulds and production of mycotoxins. The results of Mokoena et al (2005) indicate that lactic acid bacteria fermentation can significantly reduce the concentration of fumonisins and zearalenone in maize. The positive effect of Lactobacillus on mould growth and aflatoxin production was reported by Gourama and Bullerman (1995).…”
Section: Discussionmentioning
confidence: 86%
“…is the class of bacteria having a significant impact on fumonisins. The FB 1 level in maize was decreased by lactic acid bacterial activity after 3-day fermentation (Mokoena et al, 2005). To determine the effect of the microorganism to fumonisins, most of the studies were conducted to estimate the impact of bacteria to fumonisin produced by Fusarium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Several Rhizopus strains, including R. stolonifer, R. oryzae, and R. microsporus, completely degrade ZEN (El-Nezami et al 2002). Mokoena et al (2005) also reported that lactic acid bacteria fermentation can significantly reduce the ZEN concentration in maize by 68-75%. However, such a reduction may not be sufficient for complete detoxification of the toxin.…”
Section: Introductionmentioning
confidence: 96%